Hydrogeochemical characteristics and water-rock interaction mechanism of coalbed-produced water in the Linfen mining area, eastern margin of Ordos Basin, China - Guo, Zhidong; Bao, Yuan; Wang, Yubin; Yuan, Yang; Li, Zhengyan; Wang, Yaya; Xia, Lin; Liu, Weibin; Ma, Jianli (Frontiers in Earth Science, 2023)
Linfen mining area is one of the main coalbed methane industrial bases in the eastern margin of Ordos Basin, China. However, there are few studies on the hydrogeochemical characteristics of coalbed-produced water in the area. This article collected water samples from 14 coalbed methane drainage wells and analyzed the ionic concentrations, hydrogen and oxygen isotopes, dissolved inorganic carbon isotopes (δ13CDIC) and trace elements. The results showed that the water of Nos. 5 and 8 coal seams are both Cl-Na type. The total dissolved solids content was high, ranging from 5011.45 mg/L to 23405.39 mg/L. Hydrogen and oxygen isotope data indicated that the coalbed-produced water in the study area is recharged from atmospheric precipitation. In addition, the HCO3− in the produced water of No. 5 coal seam and No. 8 coal seam was negatively correlated with δ13CDIC. The value δ13CDIC in the produced water of No. 5 coal seam was heavier than that of No. 8 coal seam. These indicate that microbial degradation occurred more strongly in No. 5 coal seam than in No. 8 coal seam. The water-rock interaction in the study area was found to be dominated by cation exchange and dissolution filtration through the relationships between anion and cation.